The behavioural aspects of budgeting in the government sectors / Suhara Kamarudin - Kamarudin, Suhara (1987)
This research has been undertaken to examine the importance of behavioural consideration in government budgeting. To dates no research has ever been carried out in this subject and there is limited information discussing on the behavioural aspect of budgeting.